IMPLEMENTATIONS OF SUNDANESE LOCAL WISDOM IN CIVIC STUDIES AS A REIFORCEMENT FOR STUDENTS’ CHARACTERS (A CASE STUDY OF JUNIOR HIGH SCHOOL STUDENTS IN SMP NEGERI 3 PURWAKARTA) - Purwanti, Metty Indah (Universitas Pendidikan Indonesia, 2017)
The objective of the study is to explore on how Sundanese local wisdoms are implemented in civic studies in reinforcing students’ characters in SMP Negeri 3 Purwakarta (Junior high school). Qualitative approach is employed in this study by conducting case study as a method of data gathering. The results of the study indicate that the learning process has been implemented ordinarily through the seven-day at school program. Despite the fact that local wisdoms are not specifically embedded into the syllabus, the local wisdoms are integrated in the daily learning process. In practice, teachers are expected to be able to give insights to their students relted to the Sundanese local wisdom. The implementation is carried out in forms of: 1) Civic studies classes; 2) extracuricullar activities; 3) having meals together, and so on. Those activities are considered as a leading way to reinforce the students’ character.